Vpliv aktivacije vnetnega odgovora na anemijo pri bolnikih s srčnim popuščanjem - Ferjan, Mateja (Medicinski razgledi, 2006)
Anemia is a common comorbidity in patients with chronic heart failure. Compared to the general population, the prevalence of anemia is much higher among hears failure patients and is increasing with severity of the disease. Anemia therefore represents a strong independent prognostic f actor of adverseoutcome in these patients. Although recent data suggests that anemia inheart failure may be related to the activation of inflammatory response, rite evidence is- inconclusive. The aim of our study was to better define the patophysiologic background and prognostic factors in patients with heart failure and anemia, and to investigate the role of inflammatory response activation in this regard. A total of 95 patients with chronic heart failure and anemia defined as hemoglobin levels below 120 g/l were enrolled in this prospective study. Based on a standard questionnaire, data on morbidity and mortality were collected over a one-year period, including information on survival times and causes of death in patients who died in that period. Patients who died within 1 year had signiflcantly lower hemoglobin levels compared to those who survived (p<0.05). Contrary to our hypothesis, however, inflammatory activation was not associated with worse 1-year survival, and higher levels of CRP were not associated with lower hemoglobin levels. However, 1-year survival in our patient cohort was significantly affected by the presence of renal insufficiency (7C,% of patients with renal insufficiencyamong the expired vs. 41% in the remaining cohort, p < 0.05). Similarly, diabetes mellitus was more frequent among the expired patients titan in those who survived (p < 0.05). (Abstract truncated at 2000 characters)
Keywords: Anemija; Heart Failure, Congestive; C-reaktivna beljakovina; Anemia; Ledvična odpoved; Survival Analysis; Preživetje, analiza; Kidney Failure; Srce, odpoved kongestivna; C-Reactive Protein; Diabetes Mellitus; ankete; Sladkorna bolezen; Questionnaires; Spolni faktorji; Age Factors; Sex Factors; Starostni faktorji; srčno popuščanje